Tempe Liquid Waste as Hydroponic Fertilizer in Sanan Village, Malang - Soni Andriawan; Anis Zubaidah; Mujiono; Fia Sulis Setiani; Alif Zidane Juni Wananda; Ahmad Uzair Baihaqi; Dimas Calvin (Jurnal Dedikasi, 2021)
The tempe industry activity in Sanan Village, Purwantoro Village, Blimbing District, Malang City creates an unpleasant odor that disturbs residents around the industry. Generally, tempe producers dispose of liquid waste from tempe production activities directly into rivers. Therefore, this activity aimed to make the community more aware of the correct management of tempe liquid waste. Making organic fertilizer from tempe liquid waste (TLW) for hydroponic technology was the primary goal of this program. Organic waste is fermented with EM4 in TLW media. Other than that, our program supports implementing urban farming in the city center to produce individual food. It is hoped that, in the future, all communities in Sanan Village can produce independent food by utilizing organic fertilizer from fermented tempeh liquid waste. The result of this program was the increase in people’s knowledge about the manufacture and setting of organic and hydroponic fertilizers. Second, the residents of Sanan Village have applied fertilizer for their hydroponics. Assistance is carried out periodically to Youth Organizations in Sanan Village, Purwantoro Village, Blimbing District, Malang City on September 9 - 20 December 2020.